Beyond Given Knowledge Investigation, Quest and Exploration in Modernism and the Avant-Gardes - Ayers, David 1960-; Bru, Sascha 1976-; Benedikt Hjartarson 1972-; Montier, Jean-Pierre; Nicol, Françoise; Veivo, Harri 1969- (European Avant-Garde and Modernism Studies, 2017)
The effort to go beyond given knowledge in different domains – artistic, scientific, political, metaphysical – is a characteristic driving force in modernism and the avant-gardes. Since the late 19th century, artists and writers have frequently investigated their medium and its limits, pursued political and religious aims, and explored hitherto unknown physical, social and conceptual spaces, often in ways that combine these forms of critical inquiry into one and provoke further theoretical and methodological innovations. The fifth volume of the EAM series casts light on the history and actuality of investigations, quests and explorations in the European avant-garde and modernism from the late 19th century to the present day. The authors seek to answer questions such as: How have modernism and the avant-garde appropriated scientific knowledge, religious dogmas and social conventions, pursuing their investigation beyond the limits of given knowledge and conceptions? How have modernism and avant-garde created new conceptual models or representations where other discourses have allegedly failed? In what ways do practises of investigation, quest or exploration shape artistic work or the formal and thematic structures of artworks?